Status of late blight disease (Phytophthora infestans) of potato at Gurez in Jammu and Kashmir - T.A. WANI and VASEEM YOUSUF, Z.A. BADRI*, NAZIR A. BHAT, F.A. RAINA, (Indian Phytopathology, 2014)
Late blight (Phytophthora infestans), was found prevalent in all the potato growing villages of Gurez with incidence 9.99 to 53.33% and 14.76 to 57.77% and intensity 6.61 to 38.90% and 5.71 to 46.75% in 2011 and 2012, respectively. The maximum mean disease incidence (24.44% in 2011 & 55.55% in 2012) and intensity (15.95 in 2011 & 42.82% in 2012) was recorded in village Wanpora of lower Gurez and minimum mean disease incidence (13.88 & 28.88% include similarly) and intensity (6.16 & 17.72%) was recorded in village Gujran of Upper Gurez. Both the late blight incidence and intensity increased with crop growth stage from flowering to dehaulming in both the years.